Tainted food—Do managers really go to jail? - Rickey E. Richardson; Laura L. Gordey; Kyle C. Post (Cogent Business & Management, 2018)
The Centers for Disease Control and Prevention (CDC) estimates that, in the United States, “each year 48 million people get sick from a foodborne illness, 128,000 are hospitalized and 3,000 die”. In recent years, causes of such illnesses have been traced to tainted fresh produce, peanut butter, ice cream, cheese, meats, flour, frozen foods, raw milk, nuts, and a wide variety of other foods. The primary responsibility to keep the food supply safe in the United States rests with the United States Department of Agriculture (USDA) and the Food and Drug Administration (FDA). In serious cases of tainted food, an investigation may result in criminal charges being pursued by the United States Department of Justice (DOJ). Prosecutions may be against a business entity, individuals working for the entity, or both. This research focuses on prosecutions reported between 1 January 2012, and 31 August 2017. Content analysis was used to analyze CDC data, press releases of the USDA, FDA, and DOJ, and court cases. Results of this study may increase awareness of managers of the potential criminal consequences of their decisions related to food production, processing, and sales, as well as more ethical business decisions.
Keywords: 650